Experimental Study of Breach Mechanics in Overtopped Noncohesive Earthen Embankments - Al-Riffai, Mahmoud (Université d'Ottawa / University of Ottawa, 2014)
A comprehensive experimental program dealing with three-dimensional overtopping and breach development as well as two-dimensional overtopping physical tests of noncohesive earth embankments has been conducted on scale models in the Hydraulic Laboratory at the Department of Civil Engineering at the University of Ottawa. The experimental program which consisted of three phases focused on geotechnical and hydraulic aspects of the embankment breach mechanism. The first two phases focused on two test series for the three-dimensional breach overtopping tests: drainage and compaction. The test series were designed to determine the embankment breach characteristics using test parameters which have not been adequately identified or controlled in past noncohesive physical models: initial soil-water state and optimum dry unit weight. Both parameters were controlled in laboratory tests by means of compaction effort and seepage through the embankment body, respectively. The dynamic compaction technique employed in the preliminary experimental phase was refined to represent a more realistic method. A novel method was thus designed to simulate the construction of a real-size prototype embankment, where a vibratory and static load was used to apply and control, respectively, the compaction effort. The hydraulic aspects of the embankment breach mechanism were also investigated. For the first time, scale series tests have been used to assess the Froude criterion using tilted and quasi-exact geometric scales under very low inflow within the scope of three-dimensional breach overtopping. Data measurements included a time-history of water surface levels and video footage captured from three locations: upstream, downstream and above the embankment models. The analysis for the spatial breach overtopping tests involved measurement of the breach outflow hydrograph and breach channel evolution at the upstream slope, using hydrologic routing and a developed photogrammetric technique using the video footage, respectively. An expression which estimates the breach outflow based on this apparent upstream control section was therefore derived. The relationship between the measured and estimated breach outflow was expressed in terms of breach discharge efficiency. The third phase of the experimental program was comprised of two-dimensional overtopping tests to investigate the erodibility of a steep slope in overtopped noncohesive embankment models. A novel experimental two-dimensional configuration used to measure the pore-water-pressures within the embankment model body was developed using micro and standard tensiometer-transducer-probe assemblies, designed, assembled and tested at the Geotechnical Engineering Laboratory. A transient flownet analysis was developed using ArcGIS and the time-history of the pore-water-pressure measurements. All flow parameters were computed using the free water surface and bed profiles captured using a photogrammetric technique and the developed hydrologic routing method. Using the one-dimensional Saint-Venant equations, an analytical expression for the bed shear stress was derived to take into account the effects of unsteady flow, boundary seepage and steep slopes. Using the measured erosion rates and the sediment continuity principle, the bed mobility relationship expressed by the Shields and transport parameters was revisited to account for the effects of unsteady and supercritical flow on a downstream steep slope in the presence of boundary seepage. This novel transient flownet approach will lead to the development of new sediment mobility relationships for breach flows, instead of the classical sediment transport-capacity formulations which are based on steady, subcritical and normal flow conditions.
Keywords: Embankment; Overtopping; Breach; Erosion; Scale Series; Noncohesive; Compaction; Seepage erosion; Earth Dams; Dikes; Hydraulic Models; Unsaturated Soil